Methods of formation readiness of the future teachers to the patriotic education of high school students - A.V. Leonenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : develop method of training of the future teachers of physical culture to the patriotic education of high school students. Material: processed more than 100 literary sources. Results : defines the main approaches to understanding the concept of «readiness» in the training of future specialists. Develop the necessity of improving the professional training of future teachers of physical culture to the profession. Pedagogical conditions of implementation methodology training of the future teachers of physical culture to the patriotic education of high school students. During the implementation phase values important to mastering these skills: improving personal skills through participation in extracurricular activities, intensify research and independent work. Conclusion : it is proved that the effectiveness of the proposed technique is defined as the result of theoretical and practical training of future specialists to patriotic and educational activities with high school students.